Discovering a 'post-revolutionary' sense of place in China's small commodity city of Yiwu. Issue 3 (4th May 2019) - Hulme, Alison
Abstract : The 'small commodity city' of Yiwu in China specialises in low-end products, enjoying economic success due to its early establishment of private enterprise, yet relying upon traditional forms of solidarity as well as those provided by the structures of the market. It has 'history', but one that has been reconstructed beyond all recognition. Drawing primarily upon the work of Doreen Massey, this article explores the burgeoning sense of place in Yiwu and the wider implications this has for thinking on place. The article analyses two specific elements: the 'Wenzhou model', on which China's small commodity economy is built, and the architectural form of the 'small district'. It argues that the use of the Wenzhou model in Yiwu situates it at the forefront of an economic national historical trajectory, and that the development of small districts, tied as they are to previous historical built forms, provides a sense of the past as an assemblage from which current identity can be forged. A sense of place, it proposes, has arisen precisely due to the unusual assemblage of those elements, but is less tied to traditional notions of place, being more grounded within moments and networks that resonate with current post-revolutionary lived experiences.